Effectiveness of Enteral Nutritional Therapy in the Healing Process of Pressure Ulcers: A Systematic Review - Gisely Blanc; Marineli Joaquim Meier; Janislei Giseli Dorociaki Stocco; Hellen Roehrs; Karla Crozeta; Dulce Aparecida Barbosa (SciELO, 2015)
OBJECTIVE To evaluate the effectiveness of enteral nutritional therapy (ENT) in the healing process of pressure ulcers (PU) in adults and the elderly. METHOD A systematic review whose studies were identified through the databases of Cochrane, MEDLINE/PubMed, SciELO, LILACS, EMBASE, CINAHL, Web of Science, and manual searches. It included randomized clinical trials (RCTs) without delimiting the period or language of publication, which addressed adults and elderly patients with pressure ulcers in a comparative treatment of enteral nutritional therapy and placebo or between enteral nutritional therapy with different compositions and dosages. RESULTS We included ten studies that considered different interventions. It resulted in more pressure ulcers healed in the groups that received the intervention. The included studies were heterogeneous with regard to patients, the type of intervention, the sample and the follow-up period, all of which made meta-analysis impossible. CONCLUSION Although the enteral nutritional therapy demonstrates a promotion of pressure ulcer healing, sufficient evidence to confirm the hypothesis was not found.